Effects of radiation leakage of microwave oven on male Swiss albino mice - N.A, ElGhazaly,; H.S, Abdel Gawad,; E.H., Radwan,; A., Barakat,; K., Kamel, (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Continuous microwave radiation leakage from microwave oven may be harmful for users who have high exposure to them. The aim of this work was to assess the effects of microwave leakage on blood, liver, kidney and testis of pre-and postpubertal male Swiss albino mice. An experimental study was conducted on control and experimental groups from both stages of mice. The experimental groups were exposed to leakage waves from oven three times a day for 30 minutes each. At the end of experiment (8weeks) blood and organs were collected for physiological, biochemical analyses. The results revealed a decrease in the experimental groups Hb and RBCs count (p< 0.05)with an increase in WBCs count(p>0.05) compared to their controls. Albumin, bilirubin and protein indicated some changes (p>0.05) meanwhile protein decreased significantly (p<0.05) in post-pubertal experimental group. ALP, ALT and AST values were increased (p<0.001) in both stages. Triglycerides were increased in both stages (p<0.001). Testosterone and LH decreased in the experimental groups than the control (p>0.05). There was a significant decrease in activity of GPx and SOD and an increase in MDA activity among the experimental groups. The present study concluded that the regular use of microwave ovens leads to negative impact upon physiological activities.